A Cross-Modal Working Memory Binding Span Deficit in Reading Disability. (March 2019) - Toffalini, Enrico; Marsura, Mara; Garcia, Ricardo Basso; Cornoldi, Cesare
Successful reading demands the ability to combine visual-phonological information into a single representation and is associated with an efficient short-term memory. Reading disability may consequently involve an impaired working memory binding of visual and phonological information. The present study proposes two span tasks for assessing visual-phonological working memory binding. The tasks involved memorizing cross-modal associations between nonsense figures and nonwords, and they were administered, with other working memory measures, to children with and without a reading disability. The tasks required recognizing which figure was associated with a given nonword and recalling which nonword was associated with a given figure. Children with a reading disability had a similar significant deficit in both cross-modal binding tasks when compared with the control children, and the difference remained significant even after controlling for other verbal and nonverbal working memory measures. The cross-modal binding tasks described here seem to capture a core aspect of working memory associated with reading and may be a useful procedure for assessing reading disabilities.